Implementation of the State Policy for the Development of the Health Care System in the Conditions of European Integration on the Basis of Risk Management Strategy - Zamchiy, Serhii (Theory and Practice of Public Administration, 2023)
The article examines the essence and peculiarities of strategic management of the development of the health care system in conditions of uncertainty and the main directions of implementation of the European integration state policy of the development of the health care system based on the risk management strategy and the assumption that the transformational processes accompanying the functioning and development of health care I encourage radical, not partial changes in the relevant system.It was found that the formation of a system of multi-level management of the functioning and development of the health care system based on risk management should cover all its subsystems and components, as well as provide for the division into several successive stages, or stages, each of which represents real changes in system during a certain period of time, taking into account the risks inherent in each level of its functioning, taking into account the interaction of various subjects, whose activities are aimed at achieving certain socially significant results.It was determined that the goal of risk management in the health care system should be considered to be the formation of a certain set of targeted measures and actions, the reduction of the actual deviation from the achievement of planned goals and objectives and the corresponding performance indicators due to the selection of a risky alternative and the minimization of losses from the risk, as well as on the basis of: using means of avoiding and reducing the degree of risk in a legal way; control and optimization of risk when it is not possible to avoid it in full; conscious acceptance of the degree of risk in the case when this decision is justified from a socio-economic, political, technological and managerial position.It is proven that under conditions of uncertainty, there is a need to build an effective risk management strategy and apply appropriate management mechanisms in the process of implementing the state policy of health care development and its integration into the European public and social space. The risk management strategy for the implementation of the state policy for the development of the health care system should be understood as a certain set of targeted measures, as well as a set of methods and means of risk identification, their forecasting and response in order to control and reduce the probability of making unreasonable decisions, the results of which may lead to negative consequences for the functioning and development of the relevant system with further analysis of the results of relevant decisions.